Negotiating transfer pricing using the Nash bargaining solution - Clempner, Julio B.; Poznyak, Alexander S. (Zielona Góra: Uniwersytet Zielonogórski)
This paper analyzes and proposes a solution to the transfer pricing problem from the point of view of the Nash bargaining game theory approach. We consider a firm consisting of several divisions with sequential transfers, in which central management provides a transfer price decision that enables maximization of operating profits. Price transferring between divisions is negotiable throughout the bargaining approach. Initially, we consider a disagreement point (status quo) between the divisions of the firm, which plays the role of a deterrent.
Keywords: negotiated transfer pricing; Nash bargaining; tax avoidance; corporate taxation